Biology and integrated management of tobacco caterpillar, Spodoptera litura Fab.: A systematic review - Sushmita Sharma; Sachin Upadhayaya; Sundar Tiwari (Future Science, 2022)
Tobacco caterpillar (Spodoptera litura) has damaged in great extent in different cultivated crops. Mainly it affects solanaceous crops. It feeds on the leaves of the crop and crops seems as it is fed by the animals. In later stage it damages whole plant causing rotting of plant. Commercial farmers are normally relying on chemical pesticides. Integrated Pest Management (IPM) strategy is suggested as a best option of pest management. Using respective trap crop of major crops has been found most effective method as trap has multiple advantages for the small-scale farmers. Handpicking can be effectively used for the fourth and fifth instar of the larva. This systematic review aims to collect the general biology of tobacco caterpillar and related species as well as various IPM measures of pest management. The details pest biology, ecology, host distribution and integrated pest management are reviewed systematically and presented in review section. Reviews were carried out citing different journal articles, books, conference proceedings, thesis, reports, books sections etc. This review can be useful for the researchers, academicians and extension workers to develop an IPM protocol for the tobacco caterpillar.